Efektivitas Program Group Dialectical Behavior Therapy (DBT) terhadap Peningkatan Kemampuan Mindfulness dan Relasi Interpersonal pada Pasien Bipolar - Setiani, Tiara Prima; Ratnasari, Yudiana (Psyche 165 Journal, 2024)
Mood disorders often occur in individuals aged 18 – 45 years and can interfere with daily activities, bipolar is one of them. The recurrence rate in bipolar disorder can reach 30-40% per year. Therefore, medication and non-medication interventions are needed. Dialetic Behavior Therapy (DBT) is a form of intervention that can help individuals regulate emotions and overcome other problems. This research in collaboration with Bipolar Care Indonesia aims to facilitate intervention needs for bipolar survivors and is also structured to ensure adaptation to the DBT module is as expected. DBT intervention was carried out on 10 individuals with bipolar disorder. This research was conducted in groups and this research only focused on mindfulness abilities and also interpersonal relationships. Quantitative data was obtained using the Mindfulness Attention Awareness Scale (MAAS) and Simple Rathus Assertiveness Scale–Short Form (SRAS-SF). Meanwhile, qualitative data was obtained from observations, interviews, sharing sessions, and feedback from participants at each session. The results of this study stated that it did not show statistically significant changes. However, qualitatively, DBT intervention was able to help participants find friends, distance themselves from negative thoughts, and increase assertive abilities.